Unraveling the Catha edulis Extract Effects on the Cellular and Molecular Signaling in SKOV3 Cells - Abou-Elhamd, Alaa Sayed; Kalamegam, Gauthaman; Ahmed, Farid; Assidi, Mourad; Alrefaei, Abdulmajeed Fahad; Pushparaj, Peter Natesan; Abu-Elmagd, Muhammad (Frontiers in Pharmacology, 2021)
Khat (Catha edulis (Vahl) Endl.) is an evergreen flowering shrub used as a stimulant in many regions worldwide including East Africa, the Arabian Peninsula, Europe, and the United States. Chewing leaves of khat induces excitement and euphoria, which are primarily attributed to two major constituents, cathinone and cathine. Khat also contains other important constituents such as cathedulins. A considerable number of studies reported side effects induced by the khat extracts to both embryos and adults. These include teratogenicity and developmental retardation, oral cancer and ulcers, high blood pressure, and myocardial infarction. So far, little attention has been paid to the effects of khat extracts on the molecular signaling interactions. We aimed in this study to investigate this through evaluating the effects of khat extracts on SKOV3, a human ovarian adenocarcinoma cell line. We show, by in vitro assays, that khat induces several cellular defects including reduced cell size, cell membrane damage, and apoptosis. At high khat extract concentrations, the cell metabolic activity, cell cycle, and cellular proliferation were affected. RT-qPCR analysis showed an increase in the gene expression of the apoptotic marker BAX, the tumor suppressor p53, and the inflammatory cytokine IL-6. Protein expression analysis by immunostaining showed downregulation of β-catenin, E-cadherin, and Ki-67 and upregulation of FZD8 and SPRY2, suggesting that Wnt and FGF signaling were implicated. SwissTargetPrediction in silico analysis showed that khat constituents cathine, cathinone, catheduline K2, and catheduline E5 bind to family A G-protein-coupled receptor, cause many neurological diseases and disorders such as Alzheimer's, schizophrenia, depression, and anxiety, and induce many ovarian cancer-related diseases. The analysis also showed that important signaling pathways such as CREB, Wnt, FGF, IL-6, and ERK/MAPK, and that of the endometrial cancer, and cell cycle were implicated. Upstream regulators of cathine and cathinone were found to potentially target several molecules including interleukin-8, MMP2, PLAU, and micro-RNAs. In conclusion, khat induces significant cellular and molecular changes that could potentially cause a wide range of serious diseases and syndromes. Such an impact could have a heavy burden on the health care system in the countries where khat is consumed.